The Contribution Of Hand Muscle Power And Wrist Flexibility To Jumping Smash Hit Skill Of Badminton Extracurricular Students At Sman 06 Mukomuko Bengkulu - Deffri Anggara; Bismi Fornandes (Hanoman Journal: Physical Education and Sport, 2020)
This is a correlational research. The population of this research is all students participating in the badminton extracurricular  at SMAN 06 Mukomuko 25 students. The sampling is done by using total sampling method which result in 25 male students. The data collection techniques are : 1) hand power is tested by one hand medicine ball put, 2) wrist flexibility is measured by using arc-ruler, 3) jumping smash hit skill is tested by using badminton court with grading boxes. The data is analysed by product moment correlation and dual correlation with α = 0.05 significance. The result of the data analysis are : 1) There is a  significant relation between hand muscle power and students jumping smash hit skill in badminton extracurricular class at SMAN 06 Mukomuko, Bengkulu and the contribution is 39,19%, 2) There is significant relation between wrist flexibility and the students jumping smash hit skill and the contribution is 38,69%, 3) There is significant contribution of both muscle power and wrist flexibility to the students jumping smash hit skill as much as 55,65%.